2018
DOI: 10.1680/jenge.15.00087
|View full text |Cite
|
Sign up to set email alerts
|

A heat energy recovery system from tunnel waste water

Abstract: Minimising the maintenance costs of water ingress in transportation tunnels is a significant challenge. Decreasing the overall cost of a ground source heat pump system is equally challenging. An effort to address both issues at once has been made in relation to groundwater ingress in the Glasgow Subway system. Inflowing water is a valuable resource which could be channelled through a water source heat pump (WSHP) to produce heat energy for domestic or public use (heating and domestic hot water). Water flow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…We have previously reported that the total heat load at St George's Cross Station was 5.2 kW (Hytiris et al, 2016). Thus, a 9kW WSHP was required to meet this station's heating and domestic hot water demand.…”
Section: Figure 4: Rainfall Vs Water Flow Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that the total heat load at St George's Cross Station was 5.2 kW (Hytiris et al, 2016). Thus, a 9kW WSHP was required to meet this station's heating and domestic hot water demand.…”
Section: Figure 4: Rainfall Vs Water Flow Comparisonmentioning
confidence: 99%
“…Once water enters the tunnel network, the flows are eventually directed to the pumping station sumps either via a drainage channel set within the concrete trackbed between the running rails or via drainage pipes, dependant on the location of sumps and discharged through a pumping system. In a previous publication (Hytiris et al, 2016) we detailed water flow and water temperature measurements carried out over a 15-month period at 21 different points within the network of the underground tunnels and platforms. The points of highest water influx were identified, and the heat energy content of each was calculated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was planned, designed and carried out on location during the last quarter of 2015. St George's Cross station's heat demand was calculated to be 5.2 kW [8]. Therefore, a 9 kW water source heat pump was necessary to cover the heating and the domestic hot water demand.…”
Section: Wastewater Readings and Wshp Installationmentioning
confidence: 99%
“…This was designed and delivered on site in late 2015 and commenced operation in the last quarter of 2015. 112-3 The total heat load at the St George's Cross Station was calculated in 5.2 kW [2]. Thus, a 9kW WSHP was required to meet this station's heating and domestic hot water demand.…”
Section: Installationmentioning
confidence: 99%